Tasawuf Kebahagiaan dalam Pandangan Al-Ghazali - Yusuf Suharto, Yusuf; Ishmatun Nihayah, Ishmatun (Mahad Aly Al Fithrah, 2021)
Happiness is a human demand from time immemorial, but human understanding of it is diverse and mostly materialistic. The study of happiness according to the perspective of the scholars becomes important, related that the position of the ulama occupies an important position in understanding Islam.This research is a qualitative research on the theory of happiness according ulama especially Imam al-Ghazali. From this research it is known that; First, happiness can only be achieved by combining knowledge and charity. Knowledge is a very important prerequisite and charity is the complement of knowledge. Second, the most important happiness is the happiness of the hereafter, while the happiness of the world is sometimes false, deceit or truth if it helps the happiness of the hereafter. Third, that happiness is achieved by gathering and synergizing the four virtues after the virtues of the hereafter, namely the virtues of the soul, the virtues of the body, the virtues of the outside, and the virtues of taufik.